2006
DOI: 10.1007/s10722-005-4500-x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in European Maize (Zea mays L.) Landraces under High and Low Nitrogen Inputs

Abstract: An European maize (Zea mays L.) landrace core collection (EMLCC) was formed with samples from several countries. Evaluation of the EMLCC may contribute to broad the genetic base of maize breeding programs. The objective of this study was to assess the variability of EMLCC under low nitrogen (N) in relation to high N input. Eighty-five landraces of the EMLCC, grouped in four maturity groups, and three check hybrids were evaluated for response to low (0 kg ha À1 ) and high (150 kg ha À1 ) N in Spain and Greece. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…The importance to crop yield of adequate soil N has been well documented, as many studies have demonstrated that low N resulted not only reduced grain yield, but also affected nutrient levels in kernels, particularly protein content (Bertin and Gallais 2000, Feil et al. 2005, Ferro et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance to crop yield of adequate soil N has been well documented, as many studies have demonstrated that low N resulted not only reduced grain yield, but also affected nutrient levels in kernels, particularly protein content (Bertin and Gallais 2000, Feil et al. 2005, Ferro et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The importance to crop yield of adequate soil N has been well documented, as many studies have demonstrated that low N resulted not only reduced grain yield, but also affected nutrient levels in kernels, particularly protein content (Bertin and Gallais 2000, Feil et al 2005, Ferro et al 2006. Interestingly, grain yield did not correlate well with any quality parameters (£0.30), suggesting that both high grain yield and superior grain quality can be produced simultaneously to some degree The correlations for the four measured traits between two high and low N treatments in two locations.…”
Section: Discussionmentioning
confidence: 99%
“…Broadening the genetic base of the elite breeding pool through introgression of additional material from European landraces might, therefore, be of great interest [6]. Extensive characterization studies of landraces for morphological traits [10], [11], early growth and cold tolerance [12][16], adaptation to low nitrogen fertilization [17], [18], and pest resistance [19], [20], often identified landraces with desirable traits. Germplasm collections of European landraces were also extensively genotyped with molecular markers to determine their origin, relatedness, and degree of genetic diversity [1], [7][9], which revealed their broad genetic diversity and potential for further mining of favorable alleles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Malvar et al (2007) assayed the capacity of accessions in the European Union Millet Landrace Collection to survive infestation by millet borers (Ostrinia nubilalis Hbn. ), an important regional pest, while Ferro et al (2007) worked with the same germplasm collection under field conditions, and analyzed productivity in high-and low-dose nitrogen situations, a high-percentage contributor to overall production costs, and a potential environmental pollutant whose presence in waterbodies can result in their eutrophication.…”
Section: Resultsmentioning
confidence: 99%
“…), importante praga regional. Ferro et al (2007) trabalharam com a mesma coleção de germoplasma em condições de campo, analisaram a produção nas situações de alta e baixa dose de nitrogênio, nutriente de maior valor para o custo de produção e que pode ser poluidor de ambiente, resultando na eutrofização de corpos d'água.…”
Section: Resultsunclassified